Comparison of telerehabilitation versus home-based video exercise in patients with Duchenne muscular dystrophy: a single-blind randomized study - KENİŞ COŞKUN, ÖZGE; ÖZTÜRK THOMAS, GÜLTEN; KARADAĞ SAYGI, NAİME EVRİM (My University, 2022)
Introduction Patients with Duchenne muscular dystrophy (DMD) have lost their access to on-site rehabilitation due to the COVID-19 pandemic. Telerehabilitation can be a viable approach for these patients to protect their muscle strength and functional status. The aim of this study is to compare telerehabilitation with home-based video exercises. Patients and methods Male, ambulatory DMD patients were randomized into telerehabilitation and video-exercise groups. Nineteen patients were included in the fnal analyses. Telerehabilitation consisted of live online exercises, while video exercise implemented a pre-recorded video as a home-based program. Both programs spanned 8 weeks, three times a week. Patients’ muscle strength with a hand-held dynamometer, Quick Motor Function Test, North-Star Ambulatory Assessment (NSAA), 6-Minute Walk Test (6MWT) and Caregiver Burden were recorded before and after treatment. Results The 6MWT of the telerehabilitation group was391.26±95.08 m before and387.75±210.93 after treatment (p=0.94) and 327.46±103.88 m before treatment and313.77±114.55 after treatment in video group (p=0.63). The mean NSAA score of the telerehabilitation group were26.70±8.04 before treatment and 25.20±11.33 after treatment (p=0.24). In the video group scores were 21.66±6.65 before to 22.00±8.61 after treatment (p=0.87). There were no signifcant changes between groups at the end of the treatments. The telerehabilitation group's neck extension, bilateral shoulder abduction, and left shoulder fexion, bilateral knee fexion and extension, bilateral ankle dorsifexion, and left ankle plantar fexion strength improved signifcantly and were better than the video group (p<0.05 for all measurements). Conclusion A telerehabilitation approach is superior in improving muscle strength than a video-based home exercise, but none of the programs improved functional outcomes in ambulatory patients with DMD.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; Life Sciences; Natural Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Gelişimsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Bilişsel Sinirbilim; Genel Sinirbilim; Sinirbilim (çeşitli); Duyusal Sistemler; İnsan Bilgisayar Etkileşimi; Nöroloji (klinik); Fizik Bilimleri; Developmental Neuroscience; Cellular and Molecular Neuroscience; Cognitive Neuroscience; General Neuroscience; Neuroscience (miscellaneous); Sensory Systems; Human-Computer Interaction; Neurology (clinical); Physical Sciences